Stock splits and reverse splits in the Brazilian capital market - Werner Lima Souza de Almeida, Daniel (2024)
Purpose: This study aims to evaluate the presence of abnormal returns due to stock splits or reverse stock splits in the Brazilian capital market context. Design/methodology/approach: The event study technique was used on data from 518 events that occurred in a 30-year period (1987–2016), comprising 167 stock splits and 351 reverse stock splits. Findings: The results revealed the occurrence of abnormal returns around the time the shares began trading stock splits or reverse stock splits at a statistical significance level of 5%. The main conclusion is that stock split and reverse stock split operations represent opportunities for extraordinary gains and may serve as a reference for investment strategies in the Brazilian stock market. Originality/value: This study innovates by including reverse stock splits, as the existing literature focuses on stock splits, and by testing two distinct “zero” dates that of the ordinary general meeting that approved the share alteration and the “ex” date of the alteration, when the shares were effectively traded, reverse split or split.